The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5946/ce.2018.056
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception after Colonoscopy: A Case Report and Review of Literature

Abstract: Intussusception after colonoscopy is an unusual complication. A MEDLINE search revealed only 7 reported cases. We present a report of a 28-year-old man who developed abdominal pain several hours after routine colonoscopy and in whom computed tomography (CT) revealed colocolic intussusception. We postulate that this condition is iatrogenic and induced by suctioning of gas on withdrawal of the colonoscope. A common observation among the reported cases was abdominal pain several hours after colonoscopy and right-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Tafner et al ( 17 ) reported that 20 of 30 pediatric intussusception patients could be safely reduced by colonoscopy, and this method is safe because it is non-invasive and the intestine can be directly observed. On the other hand, it has been reported that intestinal intussusception develops iatrogenically after TCS, and further investigation is required for the reduction in intussusception on TCS ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tafner et al ( 17 ) reported that 20 of 30 pediatric intussusception patients could be safely reduced by colonoscopy, and this method is safe because it is non-invasive and the intestine can be directly observed. On the other hand, it has been reported that intestinal intussusception develops iatrogenically after TCS, and further investigation is required for the reduction in intussusception on TCS ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2 One possible mechanism is a “vacuum effect” that may be induced during the concomitant aspiration of gas and retrieval of the colonoscope, which creates the possibility for a segment of proximal bowel to invaginate on a segment of distal bowel. 4 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…Intussusception results from the change of normal peristalsis by a lesion in the gut wall that induces invagination; it is demarcated as the invagination of one segment of the bowel into an immediately adjacent segment. The intussusceptum denotes the proximal segment that invaginates into the distal segment, or the intussuscipiens (recipient segment) [7].…”
Section: Discussionmentioning
confidence: 99%